EBV-specific CD8 T lymphocytes and B cells during glatiramer acetate therapy in patients with MS. Issue 6 (November 2020) - Guerrera, Gisella; Ruggieri, Serena; Picozza, Mario; Piras, Eleonora; Gargano, Francesca; Placido, Roberta; Gasperini, Claudio; Salvetti, Marco; Buscarinu, Maria Chiara; Battistini, Luca; Borsellino, Giovanna; Angelini, Daniela F.
Abstract : Objective: Infection with Epstein-Barr virus (EBV) has been associated with clinical activity and risk of developing MS. The purpose of this study is to investigate the impact of glatiramer acetate (GA) therapy on EBV-specific immune responses and disease course. Methods: We characterized EBV-specific CD8 T lymphocytes and B cells during disease-modifying treatments in 2 groups of patients with MS. We designed a 2-pronged approach consisting of a cross-sectional study (39 untreated patients, 38 patients who had undergone 12 months of GA treatment, and 48 healthy donors compatible for age and sex with the patients with MS) and a 12-month longitudinal study (35 patients treated with GA). CD8 EBV-specific T cells and B lymphocytes were studied using pentamers and multiparametric flow cytometry. Results: We find that treatment with GA enhances viral recognition by inducing an increased number of circulating virus-specific CD8 T cells ( p = 0.0043) and by relieving their features of exhaustion ( p = 0.0053) and senescence ( p < 0.0001, p = 0.0001). B cells, phenotypically and numerically tracked along the 1-year follow-up study, show a steady decrease in memory B-cell frequencies ( p = 0.025), paralleled by an increase of the naive B subset. Conclusion: GA therapy acts as a disease-modifying therapy restoring homeostasis in the immune system, including anti-EBV responses.